Invasive listeriosis outbreaks and salmon products: a genomic, epidemiological study - Raskit Lachmann; Sven Halbedel; Stefanie Lüth; Alexandra Holzer; Marlen Adler; Ariane Pietzka; Sascha Al Dahouk; Klaus Stark; Antje Flieger; Sylvia Kleta; Hendrik Wilking (Emerging Microbes and Infections, 2022)
Invasive listeriosis, caused by Listeria (L.) monocytogenes, is a severe foodborne infection, especially for immunocompromised individuals. The aim of our investigation was the identification and analysis of listeriosis outbreaks in Germany with smoked and graved salmon products as the most likely source of infection using whole-genome sequencing (WGS) and patient interviews. In a national surveillance programme, WGS was used for subtyping and core genome multi locus sequence typing (cgMLST) for cluster detection of L. monocytogenes isolates from listeriosis cases as well as food and environmental samples in Germany. Patient interviews were conducted to complement the molecular typing. We identified 22 independent listeriosis outbreaks occurring between 2010 and 2021 that were most likely associated with the consumption of smoked and graved salmon products. In Germany, 228 cases were identified, of 50 deaths (22%) reported 17 were confirmed to have died from listeriosis. Many of these 22 outbreaks were cross-border outbreaks with further cases in other countries. This report shows that smoked and graved salmon products contaminated with L. monocytogenes pose a serious risk for listeriosis infection in Germany. Interdisciplinary efforts including WGS and epidemiological investigations were essential to identifying the source of infection. Uncooked salmon products are high-risk foods frequently contaminated with L. monocytogenes. In order to minimize the risk of infection for consumers, food producers need to improve hygiene measures and reduce the entry of pathogens into food processing. Furthermore, susceptible individuals should be better informed of the risk of acquiring listeriosis from consuming smoked and graved salmon products.